Bullying Hingga Kekerasan, Masa Depan Anak Usia Dini Mulai Terancam - Hayani Wulandari; Jihan Nurul Afifah (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study uses a qualitative descriptive analysis method with a study of literature or library research. The purpose of this research is to find out, examine, and reveal problems related to bullying and violence in early childhood. Several cases were found in various regions of Indonesia with the perpetrators being teachers and peers in PAUD education units. The level of violence that occurs in Early Childhood is still experiencing spikes that have not subsided. Various factors, especially parenting style, are involved in causing violence against children. Both as victims and perpetrators that have a negative impact on the growth and development of children. Prevention efforts and the best solutions from the government and society are encouraged to create a safe and bright future for children.